Mitochondrial Redox Status Regulates Glycogen Metabolism via Glycogen Phosphorylase Activity - Ikko Sakamoto; Shuichi Shibuya; Hidetoshi Nojiri; Kotaro Takeno; Hiroshi Nishimune; Keisuke Yaku; Takashi Nakagawa; Muneaki Ishijima; Takahiko Shimizu (Antioxidants, 2024)
Mitochondria and glycogen are co-distributed in skeletal muscles to regulate the metabolic status. Mitochondria are also redox centers that regulate the muscle function during exercise. However, the pathophysiological relationship between the mitochondrial redox status and glycogen metabolism in the muscle remains unclear. In the present study, we examined the pathological effects of mitochondrial dysfunction induced by mitochondrial superoxide dismutase (SOD2) depletion on glycogen metabolism. We found that muscle glycogen was significantly accumulated in association with motor dysfunction in mice with a muscle-specific SOD2 deficiency. Muscle glycogen phosphorylase (GP-M) activity, which is a key enzyme for glycogen degradation at times when energy is needed (e.g., during exercise), was significantly decreased in the mutant muscle. Moreover, the GP-M activity on normal muscle sections decreased after treatment with paraquat, a superoxide generator. In contrast, treatment with antioxidants reversed the GP-M activity and motor disturbance of the mutant mice, indicating that GP-M activity was reversibly regulated by the redox balance. These results demonstrate that the maintenance of the mitochondrial redox balance regulates glycogen metabolism via GP-M activity.